2014
DOI: 10.1111/pai.12167
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency is associated with diagnosis and severity of childhood atopic dermatitis

Abstract: Vitamin D deficiency and insufficiency are prevalent in Hong Kong Chinese children. Vitamin D deficiency is associated with childhood AD and high total IgE. Serum 25(OH)D levels correlate inversely with both long- and short-term AD severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
80
3
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 40 publications
12
80
3
5
Order By: Relevance
“…The consistency of such a finding in a large number of studies [5][6][7][17][18][19][20][21][22], confirms that the low level of calcidiol in such a disease is not a coincidence, and that calcidiol deficiency has a possible role in the pathogenesis of AD. The controversy in the serum level of calcidiol in AD patients is mainly viewed among adult AD patients, where several studies showed the non-significant alteration of calcidiol levels among patient and control groups [8,9].…”
Section: Groupmentioning
confidence: 52%
“…The consistency of such a finding in a large number of studies [5][6][7][17][18][19][20][21][22], confirms that the low level of calcidiol in such a disease is not a coincidence, and that calcidiol deficiency has a possible role in the pathogenesis of AD. The controversy in the serum level of calcidiol in AD patients is mainly viewed among adult AD patients, where several studies showed the non-significant alteration of calcidiol levels among patient and control groups [8,9].…”
Section: Groupmentioning
confidence: 52%
“…Vitamin D deficiency, which was prevalent in local children, 6 was a significant covariate for this finding.…”
Section: Letters To the Editormentioning
confidence: 64%
“…These results echoed those of our recent study in which low serum vitamin D level was highly prevalent in both Hong Kong children with eczema and non-allergic controls. 24 Vitamin D deficiency was associated with disease severity in our eczema children. Our study found eczema severity to be associated with several single-nucleotide polymorphisms of vitamin D pathway genes.…”
Section: Discussionmentioning
confidence: 99%